Specifika psichologiceskogo soprovoždenija sportivnoj kar'ery junogo futbolista - Kostikova, N. V.; Ulyaeva, L. G. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2014)
The article considers the specifics of psychological support of sports career of a young football player. It shows the results of studies of young players` peculiarities of personalities, which are significant for psychological and pedagogical training of sports reserve.